The Effect of A-PIK (Anti Senile) Gymnastics on the Quality of Life in People with Dementia - Charish Rachmatullah; Fitri, Mustika (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2023)
Understanding the standard of quality of life is seen globally so that the quality of life is studied to grow including in the elderly. The quality of life is made an important concept for a criterion that evaluates problems in health services. The elderly often have some body functional problems that cannot be avoided, in this case the elderly who still often do physical activity can maintain the body's function to be healthier compared to the elderly who do not often do physical activity. Physical activity is actually an activity that should not be left behind from everyday life. One sign of a person's health is that by carrying out physical activity. Someone who runs physical activity and has a high level of activity can have good health and quality of life. The purpose of this study is to examine the effect of A-PIK exercise on the quality of life in people with dementia. In this study using experimental research methods in the form of pre -experiment design. Participants involved in this study were people with dementia from Cibeunying Kidul District, Padasuka Village and managed by Posbindu (Integrated Post) named Tanjung. The population in this study totaled 69 people with a sample of 22 people. Based on this research, results have been obtained that indicate that there is a significant influence on the quality of life in people with dementia after being given A-PIK exercise treatment. Keywords: Quality of Life, Physical Activity, Elderly